Clinical predictors of frequent patient telephone calls in Parkinson’s disease - Liu, Anli A.; Boxhorn, Christine E.; Klufas, Michael A.; Christos, Paul J.; Thorne, Jeffrey T.; Shih, Angela Y.; Tsankova, Nadejda M.; Dorfman, Benjamin J.; Henchcliffe, Claire; Piboolnurak, Panida; Nirenberg, Melissa J. (Parkinsonism & related disorders, 2011)
Patient telephone calls are a major form of unreimbursed healthcare utilization in Parkinson’s disease (PD), yet little is known about potential risk factors for frequent calling behavior. Prospective cohort study of 175 non-demented outpatients with PD. Our primary outcome measure was the frequency of patient telephone calls over a three-month period relative to baseline demographics, State-Trait Anxiety Index (STAI) and Beck Anxiety Inventory (BAI) scores, Unified Parkinson’s Disease Rating Scale (UPDRS) motor scores, and medication use. Based on the median call rate (1 call/3 months), subjects were dichotomized into frequent (≥2 calls) and infrequent (≤1 call) caller groups. A total of 297 calls were received, of which 264 (89%) were from the frequent caller group ( n = 63 subjects), and only 33 (11%) were from the infrequent caller group ( n = 112 subjects). Compared with calls from infrequent callers, those from frequent callers more commonly related to somatic symptoms of PD (46.8% vs. 19.4%, p = 0.007). In multivariate logistic regression analysis, independent predictors of frequent calling were: anxiety (STAI ≥55; adjusted OR = 2.62, p = 0.02), sleep disorders (adjusted OR = 2.36, p = 0.02), dyskinesias (adjusted OR = 3.07, p = 0.03), and dopamine agonist use (adjusted OR = 2.27, p = 0.03). Baseline demographics, UPDRS motor scores, and levodopa use were similar in both groups. Frequent patient telephone calls in PD are independently associated with anxiety, sleep disorders, dyskinesias, and dopamine agonist use, with a minority of patients accounting for the majority of calls. Aggressive treatment of these non-motor symptoms and motor complications might potentially reduce the burden of patient telephone calls in PD.